Julgamento antecipado da parcela madura do mérito sob a ótica da efetividade do acesso à justiça - Mano, Lilian Rodrigues (2016)
The dissertation encompass the thematic examination of the anticipated decision regarding the ripe aspect of the merit, grounded upon the strict observance of the access to Justice constitutional principle, considered in its entirety. Therefore, focusing on the constitutional tutelage of the civil procedure, and the impossibility of conceiving the procedural dictates disengaged from constitutional law, the necessary premises regarding the development of the study were established, with a brief approach to the access to Justice principle, allocating special attention to the evolution of the concept and the scope attributed to it, following the yearnings of the modern procedural theories, demonstrating that it is inherent to the principle the notion of the effectiveness of the process, which must constitute an adequate mean to the realization, on the factual level, of the substantive rights proclaimed by the State and, yet, comprising the content of the reasonable duration of the process guarantee. From them on, the paper addresses the possibility of the anticipated decision regarding the ripe aspect of the merit, de lege lata, even before the creation of the Civil Procedure Code of 2015, highlighting the dispute around article 273, §6º, of the Civil Procedure Code of 1973. Following that, the study centers on the definition of the judicial rulings with relevant decisional content (interlocutory decision and judgement) within the Brazilian legal order, deriving from an attempt of framing the partial decision of the merit within one of these species of jurisdictional ruling, considering the civil procedural system of 1973, alongside the changes promoted over it, addressing the difficulties involved in such task, the consequences of this position on the appeals and also relative to the motions to set aside judgement, as well as aspects on the execution of the ruling. The final chapter is aimed at the New Civil Procedure Code provisions which keep compatibility with the immediate decision of the ripe aspect of the merit, in order to clearly demonstrate how some innovations brought upon maintain harmony with the attendance of the access to Justice principle contents, without leaving the necessary criticism to the perpetuation of the uproar or inadequate destination, in certain points, of different rules on total and partial judgment of the merit